The Implementation of Hospital Service Data Reporting (RL 3.1) in SIRS Online is Reviewed from Facilities and Infrastructure at RSIA Artha Mahinrus Medan in 2024 - Nainggolan, Ade Sherevina; Valentina, Valentina; Ritonga, Zulham Andi (COVID-19 : Journal of Health, Medical Records and Pharmacy, 2024)
Hospital reporting is an organizational tool that aims to produce fast, precise, and accurate reports. This study aims to identify the factors that hinder the reporting of hospital service data (RL 3.1) at RSIA Artha Mahinrus Medan, as well as evaluate the impact of the condition of facilities and infrastructure on the effectiveness of the reporting process using the online SIRS application, by considering three indicators of infrastructure: completeness, condition, and use. The approach used is qualitative descriptive, with data collection through interviews and observations of research subjects including the head of medical records, registration officers, poly officers/nurses, and IT officers. The instruments used are interview guidelines and observation sheets. The results of the study show that the reporting of hospital service data (RL 3.1) in the online SIRS at RSIA Artha Mahinrus Medan experienced obstacles, such as the lack of number of computers in the medical record unit, computer system failures, and limited internet connections, which caused slow networking. Based on the results of the study, delays in making reports can be caused by problems with existing facilities and infrastructure. Therefore, the researcher suggests that the reporting of hospital service data (RL 3.1) be carried out outside of the collection time to prevent additional delays.